2020
DOI: 10.3390/agronomy10122011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Various Forms of Nitrogen Fertilization and Meteorological Factors on Nitrogen Compounds in Soil under Laboratory Conditions

Abstract: Nitrogen is one of the main factors that shapes soil fertility and the productivity of crops, although its abundance can also cause damage to the environment. The aim of this study is to evaluate the influences of different forms of nitrogen fertilizers, soil temperature, and precipitation on the changes of nitrogen compounds (N-NH4+, N-NO3−, and Nmin) in two soil layers. Two pot experiments are performed, involving simulated precipitation levels of 10- and 20 mm. Urea and ammonium nitrate fertilizers are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…However, digestate increased the N-NH 4 contents. Other researchers have reported that the highest N-NH 4 content was found at 15 • C, with a decrease at 20 • C due to nitrification and possibly more intensive evaporation of NH 3 [33]. It has been suggested that the N-NH 4 content in soil is dependent on fertilizer form and temperature, with negligible migration to the deeper soil layer [34], contrary to our study.…”
Section: Discussioncontrasting
confidence: 98%
“…However, digestate increased the N-NH 4 contents. Other researchers have reported that the highest N-NH 4 content was found at 15 • C, with a decrease at 20 • C due to nitrification and possibly more intensive evaporation of NH 3 [33]. It has been suggested that the N-NH 4 content in soil is dependent on fertilizer form and temperature, with negligible migration to the deeper soil layer [34], contrary to our study.…”
Section: Discussioncontrasting
confidence: 98%
“…At the same time, there was less rainfall in the long compared to short rains, which may have reduced leaching of nutrients. High rainfall and temperatures increase N mobility [61]. In testing the efficacy of wet olive pomace in wheat varieties, Localla et al, (2019) found an increase in the concentration of grain protein content in the Aureo cultivar with increase in pomace treatment.…”
Section: Effect Ofmentioning
confidence: 99%
“…The amount of nitrogen present in soil fractions depends mainly on meteorological conditions and agrotechnical treatments. The dynamics of nitrogen are determined primarily by meteorological conditions (temperature, precipitation) and the rhythm of plant development and the forms of nitrogen fertilisers used (Trawczyński 2016;Dromantienė et al 2020).…”
Section: Physico-chemical Soil Propertiesmentioning
confidence: 99%